Mapping clinician perspectives on pediatric chronic pain needs in Spain - De la Vega, Rocío; Fernández-González, Adrían; Serrano-Ibáñez, Elena Rocío (Sage Open, 2026)
Chronic pain is a significant public health issue, particularly prominent in pediatric populations due to limited access to validated treatments. The World Health Organization emphasizes the necessity of identifying the needs of children as a foundational step in developing effective treatments. This study aims to identify the healthcare needs of children with chronic pain, including perceived needs, barriers, and facilitators identified by clinicians. Two online focus groups were conducted with nine healthcare professionals from six pediatric hospitals across all Spain. The Public and Patient Engagement Evaluation Tool (PPEET) was used to evaluate participants' experiences. Data were analyzed qualitatively using a framework analysis based on the Consolidated Framework for Implementation Research (CFIR), with the integration of the biopsychosocial model of pain and the Capability, Opportunity and Motivation Model of Behavior Change (COM-B). Clinicians identified key unmet needs in access to multidisciplinary treatment, school support, and family guidance. Barriers included fragmented services, lack of coordination across levels of care, and insufficient training. Facilitators included clinician motivation, informal professional networks, and openness to digital health tools. Findings highlight critical gaps in pediatric chronic pain care in Spain and point to strategies for service development, training, and policy initiatives. Integrating implementation science with clinical and behavioral frameworks offers a pathway to improve access and quality of care.
Keywords: Dolor; Niños; Chronic pain; Pediatric pain; Needs assessment; Focus group; Healthcare professionals